2006
DOI: 10.1152/ajpcell.00474.2005
|View full text |Cite
|
Sign up to set email alerts
|

Human esophageal microvascular endothelial cells respond to acidic pH stress by PI3K/AKT and p38 MAPK-regulated induction of Hsp70 and Hsp27

Abstract: The heat shock response maintains cellular homeostasis following sublethal injury. Heat shock proteins (Hsps) are induced by thermal, oxyradical, and inflammatory stress, and they chaperone denatured intracellular proteins. Hsps also chaperone signal transduction proteins, modulating signaling cascades during repeated stress. Gastroesophageal reflux disease (GERD) affects 7% of the US population, and it is linked to prolonged esophageal acid exposure. GERD is characterized by enhanced and selective leukocyte r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 62 publications
2
50
0
1
Order By: Relevance
“…Therefore, p38MAPK is definitely upstream of the augmented HSF1 activity. Stresses other than heat like hypoxia (Uehara et al 1999) or low pH (Rafiee et al 2006) have been observed to raise Hsp70 levels along with an increased activity of p38MAPK. Low pH causes human esophageal endothelial cells to overexpress Hsp70 by increasing HSF1 transcriptional activity through mediation by p38MAPK and Akt (Rafiee et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, p38MAPK is definitely upstream of the augmented HSF1 activity. Stresses other than heat like hypoxia (Uehara et al 1999) or low pH (Rafiee et al 2006) have been observed to raise Hsp70 levels along with an increased activity of p38MAPK. Low pH causes human esophageal endothelial cells to overexpress Hsp70 by increasing HSF1 transcriptional activity through mediation by p38MAPK and Akt (Rafiee et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Stresses other than heat like hypoxia (Uehara et al 1999) or low pH (Rafiee et al 2006) have been observed to raise Hsp70 levels along with an increased activity of p38MAPK. Low pH causes human esophageal endothelial cells to overexpress Hsp70 by increasing HSF1 transcriptional activity through mediation by p38MAPK and Akt (Rafiee et al 2006). However, in alkalosis, increase of Hsp70 levels were not accompanied by augmented p38MAPK activation (Stathopoulou et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5A and B). Similarly, PI3K has been shown to participate in phosphorylation or induction of HSP27 in response to various stimuli, including acidic pH stress-induced HSP27 induction in human esophageal microvascular endothelial cells, vasopressininduced HSP27 phosphorylation in aortic smooth muscle A10 cells, and sphingosine 1-phosphate-stimulated HSP27 induction in osteoblasts (34)(35)(36). In addition, PI3K pathway has been demonstrated as the critical mediator in p53 activation in response to cisplatin (14).…”
Section: Heat Shock-activated Akt/pkb and Erk1/2 Pathways Play A Critmentioning
confidence: 99%